Managing severe thrombocytopenia in co-infection of COVID-19 and dengue hemorrhagic fever: a case report - Theodora, Agnes; Suryana, Ketut (International Journal of Advances in Medicine, 2022)
COVID-19 pandemic in dengue endemic countries has becoming a concern due to its similarities in early clinical symptoms and laboratory features. The cases of co-infection between the two diseases are inevitable and associated with higher morbidity and mortality. Here we presented a case of a 28 years old female diagnosed with co-infection of COVID-19 and dengue hemorrhagic fever that complicated with severe thrombocytopenia and spontaneous bleeding. She came with fever that started 3 days prior to admission. Laboratory examination showed leucopenia, thrombocytopenia, elevated liver enzymes, and D-dimer. Patient tested positive for non-structural protein 1 (NS-1) dengue antigen. She had a pre-screening rapid test for COVID-19 as part of hospital protocol, and she tested positive. Followed by positive COVID-19 reverse transcriptase-polymerase chain reaction (RT-PCR) test confirming the diagnosis. During admission, patient started menstruating, resulting in active spontaneous bleeding while platelet counts dropped to below 10×109/l. Patient was given platelet transfusion, supportive therapy and put under close monitoring. The case of co-infection between COVID-19 and dengue is inevitable in tropical and sub-tropical countries. Both infections shared similar pathophysiology through different mechanism, such as plasma leakage, thrombocytopenia, and coagulopathy. Complications may arise and physician must aware of the therapeutical approach. Diagnostic testing must not be withheld when there was suspicion towards the infection. Prompt treatment and close monitoring can result in good prognosis.